Evaluation of Demographic, Histopathologic and Radiological Features of Thyroid Cancer Patients - Deger, Ozgur; Hakki Ersoy, Ismail; Aksu, Oguzhan; Kale Koroglu, Banu; Metin Ciris, Ibrahim; Numan Tamer, Mehmet (Annals of Medical Research, 2021)
Aim: Our aim of this retrospective study was to evaluate the demographic, histopathologic and radiological features of thyroid cancer patients.